2011
DOI: 10.1111/j.1365-2699.2011.02501.x
|View full text |Cite
|
Sign up to set email alerts
|

The Central American land bridge as an engine of diversification in New World doves

Abstract: Aim  The closure of the Central American land‐bridge connection between North and South America 3.5 million years ago was a major biogeographic event that allowed considerable interchange of the previously isolated faunas of these continents. However, the role that this connection may have had in diversification of North and South American faunas is less well understood. The goal of this study was to evaluate the potential role of the formation of this land connection in generating diversity, through repeated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 19 publications
4
54
2
Order By: Relevance
“…Previous studies suggested that Columbicola feather lice diversified mainly in the Paleogene [28,29]. Thus, if replacements have occurred, they must have occurred since this time.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that Columbicola feather lice diversified mainly in the Paleogene [28,29]. Thus, if replacements have occurred, they must have occurred since this time.…”
Section: Discussionmentioning
confidence: 99%
“…473 Closure of the Panama isthmus has been estimated at 3.5 mya 474 (Coates and Obando, 1996), but it has recently been suggested that 475 some dispersal across the closing isthmus was possible from 12 to 476 20 mya onwards (Farris et al, 2011). Thus, many avian taxa with 477 CA colonization events, such as the core tanagers (Sedano and 478 Burns, 2009), doves (Johnson and Weckstein, 2011), even theoret-479 ically low-dispersal species such as Sclerurus (d' Horta et al, 2013), 480 and Megascops all took place before the final closure of the isthmus. 481 The reconstruction suggesting that the Amazon forest species Andes.…”
mentioning
confidence: 97%
“…In this biogeographic scenario, methods such as dispersal-vicariance analysis (DIVA) that assume vicariance as the null model are inappropriate. Such models are biased toward vicariance events, and could therefore incorrectly attribute a speciation event to vicariance rather than to dispersal (see Weckstein 2011 andBess et al 2014 for further rationale). In this case, North America and South America came into contact, rather than separating from each other, so scenarios that posit vicariance are not biogeographically plausible.…”
Section: Biogeographic Analysismentioning
confidence: 98%
“…Due to their ability to fly, avian dispersal between continents was sometimes suggested to be uninhibited by the water barrier that existed prior to land bridge formation (Voelker 1999, Lomolino et al 2006, and the sparse avian fossil record has made it difficult to prove otherwise (Vuilleumier 1985). However, several historical biogeographic reconstructions of Neotropical and Nearctic bird species based on molecular data have indicated that many species were hindered from dispersing between continents due to the water barrier ( Barker 2007, Burns and Racicot 2009, Sedano and Burns 2010, Johnson and Weckstein 2011, Pulgarin-R et al 2013. Instead, the timing of dispersal events appears similar to that of mammals, soon after land bridge formation (Smith and Klicka 2010).…”
Section: Introductionmentioning
confidence: 96%